Let P ( x ) = x 2 − 3 x − 9 . A real number x is chosen at random from the interval 5 ≤ x ≤ 1 5 . The probability that ⌊ P ( x ) ⌋ = P ( ⌊ x ⌋ ) is equal to e a + b + c − d , where a , b , c , d , and e are positive integers. Find a + b + c + d + e .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Looking at the left side of the equation, we know that the value of the equation is an integer, which means that P ( ⌊ x ⌋ ) is an integer. ⌊ x ⌋ must assume any value of {5, 6, 7, ..., 12, 13, 14}, because 5 ≤ x ≤ 1 5 , so we evaluate P ( k ) for k in of {5, 6, 7, ..., 12, 13, 14} and we see that only for k = 5 , k = 6 and k = 1 3 that value is integer.
That means that ⌊ P ( x ) ⌋ must be 1 , 3 or 1 1 , so, P ( x ) will be some value in [ 1 , 2 ] , [ 3 , 4 ] or [ 1 1 , 1 2 ] and P ( x ) will be some value in [ 1 , 4 ] , [ 9 , 1 6 ] or [ 1 2 1 , 1 4 4 ] . Solving the three inequalities we obtain the answer.
Problem Loading...
Note Loading...
Set Loading...
Since
⌊ P ( x ) ⌋ = P ( ⌊ x ⌋ ) ∈ N ( ⋆ ) ,
than the only x ∈ A = [ 5 , 1 5 ] satisfying P ( x ) ∈ N are x 1 = 5 , x 2 = 6 , x 3 = 1 3 . Let's explain the meaning of ( ⋆ ) with an example: we see that P ( 5 ) = 1 . We also see that P ( 5 . 3 ) = 1 . 7 8 6 0 5 . . . , so ⌊ P ( 5 . 3 ) ⌋ = 1 , satisfying ( ⋆ ) . Our goal is to find all the x i + ϵ , ϵ < 1 , i = { 1 , 2 , 3 } such that ( ⋆ ) holds. For example, to find all the 5 + ϵ , we impose that
x 2 − 3 x − 9 = 2 ⟹ x = 2 1 ( 3 + 6 1 ) ≈ 5 . 4 0 5 1 . . .
It means that, for every x ∈ L 1 = [ 5 , 2 1 ( 3 + 6 1 ) ) , ( ⋆ ) holds. Let's apply the same procedure to x 2 and x 3 ; we get
L 2 = [ 6 , 2 1 ( 3 + 1 0 9 ) )
L 3 = [ 1 3 , 2 1 ( 3 + 3 6 9 ) )
If we call L = L 1 ∪ L 2 ∪ L 3 , than
P ( L ) = L e n g h t ( A ) L e n g h t ( L ) = 1 0 ( 2 1 ( 3 + 6 1 ) − 5 ) + ( 2 1 ( 3 + 1 0 9 ) − 6 ) + ( 2 1 ( 3 + 3 6 9 ) − 1 3 ) = 2 0 1 0 9 + 6 1 + 6 2 1 − 3 9
Eventually,
a = 1 0 9 , b = 6 1 , c = 6 2 1 , d = 3 9 , e = 2 0 , a + b + c + d + e = 8 5 0